Secret Key Agreement for SISO Visible Light Communication Systems - Dongqin Guo; Jian Zhang; Gang Xin; Keming Tian; Xingyu Xiao (Photonics)
This paper studies the use of secret key agreement for single-input single-output (SISO) visible light communication (VLC) systems. Specifically, we put forward a scheme for secret key generation and analyze the secret key rate in SISO VLC systems. First, we derive the secret key capacity bounds. Then, we analyze the achievable secret key rate distribution versus the illegal receiver’s location when the legal receiver’s location is fixed. Meanwhile, we deduce the average secret key capacity using random geometry knowledge when all the receivers’ positions are unknown. We also analyze the impact of employing a protected zone on the average secret key capacity and observe that a protected zone can obviously improve the secret performance. Finally, simulations are presented to verify the theoretical analysis.